POTENSI KANDUNGAN BAHAN-BAHAN ALAMI UNTUK PROSES PENYEMBUHAN LUKA : LITERATUR REVIEW - Erwin Purwanto; M. Alfian Rajab; Rini Angraini (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2023)
Background: Wounds are a problem that often occurs in every individual, the process of wound healing in each individual has the same process or stages, but the time and results of healing are very dependent on the biological condition of each individual. Wound care is a series of processes of treating wounds with various existing methods to speed up the wound healing process. Wound care using natural products has been used, but it has not been explained in detail regarding the ingredients and substances contained in natural ingredients that play a role in the wound healing process. Design: This study uses the literature review method, by summarizing the results of previous studies. Results: From the 11 articles reviewed, various kinds of natural ingredients were identified including capsaicin, betacyanin, tannins, saponins, terpenoids, flavonoids, phenolic acids, and tocopherol. The content of these natural ingredients has a positive effect when used as a wound care material. Conclusion: The content of these substances has several activities that can be used in the wound healing process such as antioxidant, anti-analgesic, anti-inflammatory, and anti-microbial activities. Suggestion: There is still a need for further research series with stronger study designs and using more studies